FUZZY INFERENCE SYSTEM METODE MAMDANI UNTUK MENGIDENTIFIKASI JENIS ALERGI PERNAFASAN SECARA DINI PADA ANAK USIA 3–6 TAHUN - Yuliana, Dyan (POLITEKNIK LP3I JAKARTA, 2019)
The incidence of allergic diseases end - the end is increased in line with the changing lifestyle of modern society. Symptoms are mild terihat trivial and sometimes make a person do not assume that allergic diseases should be dealt with immediately or serious, in fact if the allergy is not treated properly and it is not known early it will lead to more severe complications of the disease such as asthma and sinusitis. Along with the advancement of technology today, there are many problems that can be solved with technology. One of them by developing an expert system application to identify early types of allergies in children aged 3-6 years, with the specification of the type of allergic rhinitis and allergic interiten persistent allergic rhinitis with fuzzy inference system mamdani models. In this study used input variables such as amount of symptoms, long the sneezing, as well as variable frequency output is the result of the diagnosis. Results from this study is the establishment of an expert system application using MatLab 2008a to identify at an early stage of allergies in children aged 3 – 6 years.Keywords: type of respiratory allergies, Allergic Rhinitis, FIS Method Mandani